Arrhythmia Induced by Positional Change Under General Anesthesia Related to Caudal Movement of the Peripherally Inserted Central Venous Catheter: A Case Report - Isao Utsumi; Tomasz Hascilowicz; Yasushi Mio; Sachiko Omi (Case Reports in Anesthesiology)
Conclusion: The case report discusses the optimal TCS and emphasizes vigilant ECG monitoring, suggesting measures to prevent these arrhythmias under general anesthesia.